An olfactory-based Brain-Computer Interface: electroencephalography changes during odor perception and discrimination - Morozova, Marina; Bikbavova, Alsu; Bulanov, Vladimir; Lebedev, Mikhail A. (Frontiers in Behavioral Neuroscience, 2023)
Brain-Computer Interfaces (BCIs) are devices designed for communication between the central nervous system and a computer. The communication can occur through different sensory modalities, and most commonly visual and auditory systems are used. We suggest that BCIs can be expanded by the incorporation of olfactory modality. To probe the modulation of EEG activity by odorants, we implemented two olfactory tasks: one that required attention to perception of odors, and the second one where participants discriminated consecutively presented odors. EEG recordings were conducted in 13 healthy participants while they performed the tasks following computer-generated verbal instructions. Respiratory activity was recorded to relate EEG modulations to the breath cycle. Theta activity responses were observed over the frontal EEG leads approximately 2 s after the inhalation. This theta activity was different depending on whether or not the inhaled air contained an odorant, and cognitive load also had an effect. We conclude that the frontal theta rhythm is reflective of the neural processing of odors. As such, it could be incorporated in the olfactory-based BCIs which take odors either as inputs or outputs. These BCIs could improve olfactory training needed for conditions like anosmia and hyposmia, and mild cognitive impairment.